MAN Insan Cendekia: Innovation in Transforming Superior Islamic Education in the 21st Century - Muhammad Al Fathoni; Martin Kustati; Nana Sepriyanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The purpose of this study is to analyze the transformation innovation of MAN Insan Cendekia as a superior madrasah. The method used by the author in this study is the library research approach. In this method, data is collected through a review of literature or library studies are analyzed and presented in the discussion. The results of the study indicate that MAN Insan Cendekia is an example of a madrasah that focuses on the development of science and technology, as well as religion. It is under the auspices of the Indonesian Ministry of Religion and aims to improve the quality of education in Indonesia. In the 21st century, MAN has developed itself as a superior madrasah that offers better and broader education, and has more modern and complete facilities. In the 21st century, MAN IC has become an example of a superior madrasah that has developed itself as a more modern and more complete educational institution, and has better facilities to support the teaching and learning process. Thus, MAN IC has become a good example for other madrasahs in Indonesia.